An ultra high performance liquid chromatography with tandem mass spectrometry method for plasma and cerebrospinal fluid pharmacokinetics of rhein in patients with traumatic brain injury after administration of rhubarb decoction. Issue 7 (April 2015) - Wang, Yang; Fan, Rong; Luo, Jiekun; Tang, Tao; Xing, Zhihua; Xia, Zian; Peng, Weijun; Wang, Wenzhu; Lv, Huiying; Huang, Wei; Liang, Yizeng; Yi, Lunzhao; et al.
<x xml:space="preserve">Abstract</x> (J. Sep. Sci. 2015, 38, 1100–1108) DOI: 10.1002/jssc.201401197 Damage of the blood‐brain barrier is a common result of traumatic brain injury. This damage can open the blood‐brain barrier and allow drug passage. An ultra‐performance liquid chromatography–tandem mass spectrometry method was established to determine the concentration of rhein in the biofluids (plasma and cerebrospinal fluid) of patients with a compromised blood‐brain barrier following traumatic brain injury after rhubarb administration. Furthermore, the pharmacokinetic profiles were analyzed. A triple‐quadruple tandem mass spectrometer with electrospray ionization was used for rhein detection. The mass transition followed was m/z 283.06→239.0. The calibration curve was linear in the concentration range of 10‐4000 ng/mL for the biofluids. The intra‐ and inter‐day precisions were less than 10%. The Relative Standard Deviation of recovery was less than 15% in biological matrices. The pharmacokinetic data showed that rhein was rapidly transported into biofluids, and exhibited a peak concentration 1 h after administration. The elimination rate of rhein was slow. The AUCcerebrospinal fluid/AUCplasma of rhein was approximately 17%, indicating that portions of rhein could pass the impaired blood‐brain barrier. The method was successfully applied to quantify rhein in the biofluids of all patients. The data presented can help to guide clinical applications of rhubarb for treating traumatic brain injury. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>